A kind of slurry for concrete and preparation method thereof
By using a slurry containing specific components in the concrete, the problem of low efficiency and poor durability in the existing technologies solved the problem of low efficiency of concrete cracks in existing technologies, and achieved efficient, economical and stable crack repair effects.
Patent Information
- Application Number
- CN202410493126.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-04-23
AI Technical Summary
Existing problems of low repair efficiency, poor structural stability, poor durability and high cost for concrete cracks.
Adopt a concrete of silicate cement, silicon ash, Babiabacteria mud, nanocroleen, calcium lactate, sodium algosyl alginate, gypsum, and compound phosphoric acid. material.
Realizing low cost, high self -repair efficiency, stability and durability concrete slurry can quickly and effectively repair the cracks and improve the overall performance of concrete.
Smart Images

Figure CN118373645B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a slurry for concrete and a preparation method thereof. Background Art
[0002] Concrete is a non-homogeneous porous material with many microstructural defects inside, showing high brittleness and low tensile strength. Under the influence of environmental factors such as long-term load, temperature fluctuations and structural effects, concrete often develops cracks of varying degrees after a period of service.
[0003] In the early stages, fresh concrete will experience problems such as autogenous shrinkage, drying shrinkage, plastic settlement, and temperature gradients caused by hydration reactions. These microscopic defects may evolve into water seepage channels in the later concrete under certain conditions. After the concrete is put into use, the hardened concrete will be affected by a variety of factors, including alkali-aggregate reaction, abnormal expansion of cement, differential settlement, creep, temperature deformation, freeze-thaw environment, carbonation environment, chloride salt and other chemical corrosion environments, etc. These factors will inevitably lead to the formation of cracks. Cracks transform concrete from a continuous body into a discrete body, providing a convenient channel for the penetration of harmful substances such as oxygen, carbon dioxide, water, chloride ions, sulfate ions, etc., thereby causing a series of adverse consequences such as deterioration of the cement matrix and corrosion of steel bars, forming a vicious cycle of "deterioration, cracking, re-deterioration, and re-cracking".
[0004] CN111072326A discloses a crack self-repairing concrete and its preparation and repair method, wherein the crack self-repairing concrete is composed of cement, fly ash, water, sand, calcium lactate, triterpenoid saponin air entraining agent, 108 cfu / mL ATCC11859 Bacillus pasteurianus solution, PVA fiber and water reducer in a mass ratio of 927.4:103:309.1:371:31:0.1:16:5:2. The crack self-repairing concrete can improve the water resistance of concrete and improve the durability of hardened concrete, but the repair method of the concrete is to use CO2 in the air as an induction, and the repair efficiency is unstable. At the same time, the crack self-repairing cycle is long, especially for larger or deeper cracks, it takes a long time to complete the repair.
[0005] Therefore, production still needs to develop concrete slurry with low cost, high self-repair efficiency, good stability and durability. Summary of the invention
[0006] The purpose of the invention is to overcome the problems of low efficiency, poor structural stability, poor durability and high cost of slurry for repairing concrete cracks in the prior art.
[0007] In order to achieve the above object, the first aspect of the present invention provides a slurry for concrete, the slurry contains the following components:
[0008] Portland cement, silica fume, Bacillus pasteurianus sludge, nanocellulose, calcium lactate, sodium alginate, gypsum and compound phosphate;
[0009] The composite phosphate is composed of sodium phosphate, potassium dihydrogen phosphate and ammonium dihydrogen phosphate;
[0010] Relative to every 100 parts by weight of silicate cement, the content of the silica fume is 2-12 parts by weight, the content of the Bacillus pasteurianus sludge is 8-12 parts by weight, the content of the nanocellulose is 4-8 parts by weight, the content of the calcium lactate is 2-3 parts by weight, the content of the sodium alginate is 0.2-0.5 parts by weight, the content of the gypsum is 2-16 parts by weight and the content of the compound phosphate is 0.2-2 parts by weight.
[0011] The second aspect of the present invention provides a method for preparing the slurry according to the first aspect, the method comprising:
[0012] (1) subjecting silicate cement, silica fume, calcium lactate, sodium alginate, gypsum and a compound phosphate to a first stirring process to obtain a powder; the compound phosphate is composed of sodium phosphate, potassium dihydrogen phosphate and ammonium dihydrogen phosphate;
[0013] (2) subjecting the Bacillus pasteurianus sludge and the nanocellulose to a second stirring treatment to obtain a liquid material;
[0014] (3) subjecting the powder and the liquid to a third stirring treatment in the presence of water to obtain the slurry;
[0015] Relative to every 100 parts by weight of silicate cement, the amount of the silica fume is 2-12 parts by weight, the amount of the Bacillus pasteurianus sludge is 8-12 parts by weight, the amount of the nanocellulose is 4-8 parts by weight, the amount of the calcium lactate is 2-3 parts by weight, the amount of the sodium alginate is 0.2-0.5 parts by weight, the amount of the gypsum is 2-16 parts by weight and the amount of the compound phosphate is 0.2-2 parts by weight.
[0016] The concrete slurry of the present invention has the advantages of low cost, high self-repairing efficiency, good stability and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The concrete slurries prepared in Example 1, Example 3 and Comparative Example 1 were artificially damaged to produce cracks of 1 mm after pouring and curing, and the cracks were self-repaired after 1 day.
[0018] Figure 2 The concrete slurry prepared in Example 1, Example 3 and Comparative Example 1 was artificially damaged to produce cracks of 1 mm after pouring and curing, and the cracks were self-repaired after 7 days.
[0019] Figure 3 The concrete slurries prepared in Example 1, Example 3 and Comparative Example 1 were artificially damaged to produce cracks of 1 mm after pouring and curing, and the cracks were self-repaired after 14 days.
[0020] Figure 4 The concrete slurries prepared in Example 1, Example 3 and Comparative Example 1 were artificially damaged to produce cracks of 1 mm after pouring and curing. Pictures of the cracks after self-repair after 21 days.
[0021] Figure 5 The concrete slurries prepared in Example 1, Example 3 and Comparative Example 1 were artificially damaged to produce cracks of 1 mm after pouring and curing, and the cracks were self-repaired after 28 days. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] As mentioned above, the first aspect of the present invention provides a slurry for concrete, the slurry contains the following components:
[0024] Portland cement, silica fume, Bacillus pasteurianus sludge, nanocellulose, calcium lactate, sodium alginate, gypsum and compound phosphate;
[0025] The composite phosphate is composed of sodium phosphate, potassium dihydrogen phosphate and ammonium dihydrogen phosphate;
[0026] Relative to every 100 parts by weight of silicate cement, the content of the silica fume is 2-12 parts by weight, the content of the Bacillus pasteurianus sludge is 8-12 parts by weight, the content of the nanocellulose is 4-8 parts by weight, the content of the calcium lactate is 2-3 parts by weight, the content of the sodium alginate is 0.2-0.5 parts by weight, the content of the gypsum is 2-16 parts by weight and the content of the compound phosphate is 0.2-2 parts by weight.
[0027] Preferably, relative to every 100 parts by weight of silicate cement, the content of the silica fume is 4-11 parts by weight, the content of the Bacillus pasteurian sludge is 8.5-11.5 parts by weight, the content of the nanocellulose is 4.3-7.7 parts by weight, the content of the calcium lactate is 2.2-2.9 parts by weight, the content of the sodium alginate is 0.25-0.45 parts by weight, the content of the gypsum is 4-14 parts by weight and the content of the compound phosphate is 0.28-1.72 parts by weight.
[0028] Further preferably, with respect to every 100 parts by weight of Portland cement, the content of silica fume is 5-10 parts by weight, the content of Bacillus pasteurianus mud is 9-11 parts by weight, the content of nanocellulose is 5-7 parts by weight, the content of calcium lactate is 2.3-2.7 parts by weight, the content of sodium alginate is 0.3-0.4 parts by weight, the content of gypsum is 5-13.75 parts by weight, and the content of compound phosphate is 0.33-1.67 parts by weight. The inventors of the present invention have found that under this preferred condition, the concrete slurry of the present invention has better repair efficiency, stability and durability.
[0029] Preferably, the concentration of Bacillus pasteurianus in the Bacillus pasteurianus sludge is 2×10 6 cell / mL-2×10 7 cell / mL.
[0030] Preferably, based on the total weight of the composite phosphate, the weight content of the sodium phosphate is 15-20wt%, the weight content of the potassium dihydrogen phosphate is 15-20wt%, and the weight content of the ammonium dihydrogen phosphate is 60-70wt%.
[0031] Preferably, the density of the nanocellulose is 1.5-1.6 g / cm 3 , length is 0.5-5μm.
[0032] Preferably, the weight average molecular weight of the sodium alginate is 160,000-360,000, and the dispersion index is 1.5-2.5. The inventors of the present invention have found that under this preferred condition, the concrete slurry of the present invention has better repair efficiency, stability and durability.
[0033] Preferably, the average diameter of the silicate cement is 3-5 μm. The inventors of the present invention have found that under this preferred condition, the concrete slurry of the present invention has better repair efficiency, stability and durability.
[0034] Preferably, the weight content of silicon dioxide in the silica fume is 90-98wt%.
[0035] Preferably, the slurry further comprises an organosilicon emulsion and / or a water reducing agent. The inventors of the present invention have found that under this preferred condition, the slurry for concrete of the present invention has better fluidity.
[0036] Further preferably, with respect to every 100 parts by weight of Portland cement, the content of silica fume is 2-12 parts by weight, the content of Bacillus pasteurianus mud is 8-12 parts by weight, the content of nanocellulose is 4-8 parts by weight, the content of calcium lactate is 2-3 parts by weight, the content of sodium alginate is 0.2-0.5 parts by weight, the content of organosilicon emulsion is 0.32-0.64 parts by weight, the content of water reducer is 0.4-3 parts by weight, the content of gypsum is 2-16 parts by weight, and the content of compound phosphate is 0.2-2 parts by weight. The inventors of the present invention have found that under this preferred condition, the concrete slurry of the present invention has better fluidity.
[0037] Preferably, the water reducer is a polycarboxylic acid water reducer.
[0038] Preferably, the organosilicon emulsion is an organosilicon emulsion containing organosilicon and / or organosilicon resin.
[0039] Preferably, the gypsum is anhydrous gypsum and / or hemihydrate gypsum.
[0040] As mentioned above, the second aspect of the present invention provides a method for preparing the slurry according to the first aspect, the method comprising:
[0041] (1) subjecting silicate cement, silica fume, calcium lactate, sodium alginate, gypsum and a compound phosphate to a first stirring process to obtain a powder; the compound phosphate is composed of sodium phosphate, potassium dihydrogen phosphate and ammonium dihydrogen phosphate;
[0042] (2) subjecting the Bacillus pasteurianus sludge and the nanocellulose to a second stirring treatment to obtain a liquid material;
[0043] (3) subjecting the powder and the liquid to a third stirring treatment in the presence of water to obtain the slurry;
[0044] Relative to every 100 parts by weight of silicate cement, the amount of the silica fume is 2-12 parts by weight, the amount of the Bacillus pasteurianus sludge is 8-12 parts by weight, the amount of the nanocellulose is 4-8 parts by weight, the amount of the calcium lactate is 2-3 parts by weight, the amount of the sodium alginate is 0.2-0.5 parts by weight, the amount of the gypsum is 2-16 parts by weight and the amount of the compound phosphate is 0.2-2 parts by weight.
[0045] According to a particularly preferred embodiment, the method comprises:
[0046] (1) performing a first stirring treatment on silicate cement, silica fume, calcium lactate, sodium alginate, a water reducing agent, gypsum and a compound phosphate to obtain a powder;
[0047] (2) subjecting the Bacillus pasteurianus sludge, nanocellulose, and silicone emulsion to a second stirring treatment to obtain a liquid material;
[0048] (3) subjecting the powder and the liquid to a third stirring treatment in the presence of water to obtain the slurry;
[0049] Relative to every 100 parts by weight of silicate cement, the amount of the silica fume is 2-12 parts by weight, the amount of the Bacillus pasteurianus sludge is 8-12 parts by weight, the amount of the nanocellulose is 4-8 parts by weight, the amount of the calcium lactate is 2-3 parts by weight, the amount of the sodium alginate is 0.2-0.5 parts by weight, the amount of the silicone emulsion is 0.32-0.64 parts by weight, the amount of the water reducer is 0.4-3 parts by weight, the amount of the gypsum is 2-16 parts by weight and the amount of the compound phosphate is 0.2-2 parts by weight.
[0050] Preferably, in step (3), the weight content ratio of material I to the water is 1:0.1-0.15; the material I is a combination of the powder and the liquid.
[0051] Preferably, the Bacillus pasteurianus sludge in the present invention is prepared by the following method:
[0052] The Bacillus pasteurianus liquid is subjected to centrifugation and separation treatment in sequence to obtain the Bacillus pasteurianus sludge. The concentration of Bacillus pasteurianus in the Bacillus pasteurianus sludge is 2×10 6 cell / mL-2×10 7 cell / mL; the centrifugal treatment conditions include: a rotation speed of 3500-4500rpm and a time of 15-20min.
[0053] The specific method of separation treatment described in the present invention is not particularly limited and can be selected according to the technical means known to those skilled in the art, which should not be construed as limiting the present invention.
[0054] At the same time, it should be noted that the first stirring treatment, the second stirring treatment and the third stirring treatment in the present invention can make the powder, the liquid and the slurry fully stirred, and the specific method is not particularly limited and can be selected according to technical means known to those skilled in the art. According to a preferred embodiment, the temperature of the first stirring treatment, the second stirring treatment and the third stirring treatment is 25-30°C.
[0055] In the following examples, unless otherwise specified, the raw materials are all common commercially available products.
[0056] Sodium alginate I: model GOS-HYF, weight average molecular weight of 167,000, dispersity index of 1.5, purchased from Qingdao Nanshan Biotechnology Co., Ltd.
[0057] Sodium alginate II: model GOS-HWF, weight average molecular weight of 356,000, dispersity index of 2.5, purchased from Qingdao Nanshan Biotechnology Co., Ltd.
[0058] Bacillus pasteurianus bacterial solution: Model B80469, purchased from Mingzhou Biotechnology Co., Ltd.
[0059] The concentration of Bacillus pasteurianus in the Bacillus pasteurianus sludge in the following examples is 2×10 7 cell / mL; gypsum is all anhydrous gypsum.
[0060] Nanocellulose I: density 1.6 g / cm 3 , length 5 μm; purchased from Northern Century Cellulose Materials Co., Ltd.
[0061] Nanocellulose II: density 1.8g / cm 3 , length 8 μm; purchased from Northern Century Cellulose Materials Co., Ltd.
[0062] Compound phosphate I: the weight content of sodium phosphate is 20wt%, the weight content of potassium dihydrogen phosphate is 20wt%, and the weight content of ammonium dihydrogen phosphate is 60wt%.
[0063] Compound phosphate II: the weight content of sodium phosphate is 10wt%, the weight content of potassium dihydrogen phosphate is 10wt%, and the weight content of ammonium dihydrogen phosphate is 80wt%.
[0064] Compound phosphate III: the weight content of sodium phosphate is 30wt%, and the weight content of diammonium phosphate is 70wt%.
[0065] Silicone emulsion: Silicone emulsion containing organic silicone, model 8016, purchased from Guangzhou Hangeng New Materials Co., Ltd.
[0066] Polycarboxylic acid water reducer: Model DP-255, purchased from Guangdong Tianfeng Defoaming Agent Co., Ltd.
[0067] Silica fume: Model Tiankai 970 silica powder, purity of 96-98.5%, purchased from Shanghai Tiankai Building Materials Technology Co., Ltd.
[0068] Example 1
[0069] (1) performing a first stirring treatment on silicate cement, silica fume, calcium lactate, sodium alginate, a polycarboxylic acid-based water reducer, gypsum and a compound phosphate to obtain a powder;
[0070] (2) subjecting the Bacillus pasteurianus sludge, nanocellulose, and silicone emulsion to a second stirring treatment to obtain a liquid material; the concentration of Bacillus pasteurianus in the Bacillus pasteurianus sludge is 2×10 7 cell / mL;
[0071] (3) subjecting the powder and the liquid to a third stirring treatment in the presence of water to obtain the slurry;
[0072] In step (3), the weight content ratio of material I to the water is 1:0.15; the material I is a combination of the powder and the liquid;
[0073] The temperatures of the first stirring, the second stirring, and the third stirring are all 25°C.
[0074] The specific details of this embodiment are shown in Table 1.
[0075] Example 2
[0076] This example uses similar methods and process conditions as Example 1, except that the amounts of raw material components are different, as shown in Table 1.
[0077] Example 3
[0078] This example uses similar methods and process conditions as Example 1, except that the amounts of raw material components are different, as shown in Table 1.
[0079] Example 4
[0080] This example uses similar methods and process conditions as Example 1, except that the amounts of raw material components are different, as shown in Table 1.
[0081] Example 5
[0082] This example uses similar methods and process conditions as Example 1, except that the amounts of raw material components are different, as shown in Table 1.
[0083] Example 6
[0084] This example uses similar methods and process conditions as Example 1, except that the amounts of raw material components are different, as shown in Table 1.
[0085] Example 7
[0086] This example uses similar methods and process conditions as Example 1, except that the amounts of raw material components are different, as shown in Table 1.
[0087] Example 8
[0088] This example uses similar methods and process conditions as Example 1, except that the content of the components of the compound phosphate is different, as shown in Table 1.
[0089] Example 9
[0090] This embodiment uses similar methods and process conditions as those of embodiment 1, except that the types of sodium alginate are different, as shown in Table 1.
[0091] Example 10
[0092] This example uses similar methods and process conditions as Example 1, except that the types of the nanocellulose are different, as shown in Table 1.
[0093] Embodiment 11
[0094] This embodiment uses similar methods and process conditions as those of Embodiment 1, except that no silicone emulsion is added, as shown in Table 1.
[0095] Comparative Example 1
[0096] This comparative example uses similar methods and process conditions as Example 1, except that the amounts of raw material components used are different, as shown in Table 2.
[0097] Comparative Example 2
[0098] This comparative example uses similar methods and process conditions as Example 1, except that the components of the composite phosphate are different, as shown in Table 2.
[0099] Table 1
[0100]
[0101] Table 2
[0102]
[0103]
[0104] Test Example 1
[0105] The various properties of the material were tested in accordance with GB / T50080-2016 "Preparation of test methods for properties of ordinary concrete mixtures", GB / T50448-2015 "Technical specification for application of cement-based grouting materials" and GB18445-2012 "Cement-based penetrating crystalline waterproof materials", and the results are shown in Tables 3 and 4.
[0106] Test Example 2
[0107] Exemplarily, two groups of embodiments and one group of comparative examples were selected to carry out crack self-repairing experiments, and the experimental method was as follows:
[0108] After the concrete pool is poured, the formwork is removed after 3 days of curing. After the concrete is cured to 70% of the design strength, the crack position is determined, and the side wall of the pool is hydraulically supported by the hydraulic jack. A sledgehammer is used to hit the outer wall corresponding to the inner jack support position until cracks appear on the side wall of the pool. The pool is filled with water to detect whether the side wall is leaking and to check the width of the artificially created cracks. Cracks with a width of 1mm are selected for grouting tests. The crack repair conditions are observed and measured after 1 day, 7 days, 14 days, 21 days and 28 days. The results are as follows: Figures 1 to 5 As shown in Table 3;
[0109] The grouting test method is: after preparing the grouting material by mixing the concrete slurry prepared in Example 1, Example 3 and Comparative Example 1 with water at a weight ratio of 0.15:1, the grouting material is injected into the crack from bottom to top at a pressure of 0.5 MPa to ensure that the grouting material is evenly diffused in the crack. After the grouting operation is completed, the grouting hole is promptly blocked to prevent the slurry from leaking out, so as to achieve full reinforcement.
[0110] Table 3
[0111]
[0112] The coatings in the table refer to the slurry
[0113] Table 4
[0114]
[0115]
[0116] Table 5
[0117] Crack width / mm Example 1 Example 3 Comparative Example 1 1 day 1 1 1 7 days 0.3 0.3 0.8 14 days 0.1 0.1 0.6 21 days 0 0 0.3 28 days 0 0 0.1
[0118] Tables 3 and 4 are the performance test results of the concrete filled with slurry prepared in the embodiment and the comparative example; compared with the comparative example, the concrete slurry prepared in the embodiment has better comprehensive effects in setting time, fluidity, compressive strength and anti-permeability than the comparative example, indicating that the concrete slurry prepared by the present invention has better effects in terms of resistance to compressive load and resistance to liquid penetration, so that the concrete slurry has excellent stability and durability; Figures 1 to 5 Table 5 is the test data of concrete slurry for ground crack repair, where Figures 1 to 5a in the figure represents the concrete slurry prepared in Example 1, b in the figure represents the concrete slurry prepared in Example 3, and c in the figure represents the concrete slurry prepared in Comparative Example 1. It can be seen from the test results that the concrete slurry of the present invention has better repair performance than the concrete slurry prepared in the comparative example, and the concrete slurry of the present invention also has the advantage of low cost.
[0119] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A slurry for concrete, characterized in that: The slurry contains the following components: Portland cement, silica fume, Bacillus pasteurianus sludge, nanocellulose, calcium lactate, sodium alginate, water reducer, gypsum and compound phosphate; The composite phosphate is composed of sodium phosphate, potassium dihydrogen phosphate and ammonium dihydrogen phosphate; Relative to every 100 parts by weight of silicate cement, the content of the silica fume is 2-12 parts by weight, the content of the Bacillus pasteurianus sludge is 8-12 parts by weight, the content of the nanocellulose is 4-8 parts by weight, the content of the calcium lactate is 2-3 parts by weight, the content of the sodium alginate is 0.2-0.5 parts by weight, the content of the water reducer is 0.4-3 parts by weight, the content of the gypsum is 2-16 parts by weight and the content of the compound phosphate is 0.2-2 parts by weight.
2. The slurry according to claim 1, characterized in that The concentration of Bacillus pasteurianus in the Bacillus pasteurianus sludge is 2×10 6 cell / mL-2×10 7 cell / mL.
3. The slurry according to claim 1 or 2, characterized in that Based on the total weight of the composite phosphate, the weight content of the sodium phosphate is 15-20wt%, the weight content of the potassium dihydrogen phosphate is 15-20wt%, and the weight content of the ammonium dihydrogen phosphate is 60-70wt%.
4. The slurry according to claim 1 or 2, characterized in that: The density of the nanocellulose is 1.5-1.6 g / cm 3 , length is 0.5-5μm.
5. The slurry according to claim 1 or 2, characterized in that: The weight average molecular weight of the sodium alginate is 160,000-360,000, and the dispersion index is 1.5-2.
5.
6. The slurry according to claim 1 or 2, characterized in that: The weight content of silicon dioxide in the silica ash is 90-98wt%.
7. The slurry according to claim 1 or 2, characterized in that: The slurry also includes silicone emulsion.
8. The slurry according to claim 1 or 2, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.
9. The slurry according to claim 7, characterized in that The organic silicone emulsion is an organic silicone emulsion containing organic silicone and / or organic silicone resin.
10. A method for preparing the slurry according to any one of claims 1 to 6 and 8, characterized in that: The method includes: (1) performing a first stirring treatment on silicate cement, silica fume, calcium lactate, sodium alginate, a water reducing agent, gypsum and a compound phosphate to obtain a powder; the compound phosphate is composed of sodium phosphate, potassium dihydrogen phosphate and ammonium dihydrogen phosphate; (2) subjecting the Bacillus pasteurianus sludge and nanocellulose to a second stirring treatment to obtain a liquid material; (3) subjecting the powder and the liquid to a third stirring process in the presence of water to obtain the slurry; Relative to every 100 parts by weight of silicate cement, the amount of the silica fume is 2-12 parts by weight, the amount of the Bacillus pasteurianus sludge is 8-12 parts by weight, the amount of the nanocellulose is 4-8 parts by weight, the amount of the calcium lactate is 2-3 parts by weight, the amount of the sodium alginate is 0.2-0.5 parts by weight, the amount of the water reducer is 0.4-3 parts by weight, the amount of the gypsum is 2-16 parts by weight and the amount of the compound phosphate is 0.2-2 parts by weight.
11. The method according to claim 10, characterized in that The method further comprises, in step (2), subjecting the Bacillus pasteurianus sludge, the nanocellulose, and the silicone emulsion to the second stirring treatment to obtain a liquid material; The amount of the organosilicon emulsion is 0.32-0.64 parts by weight per 100 parts by weight of the silicate cement.
12. The method according to claim 10 or 11, characterized in that: In step (3), the weight content ratio of material I to the water is 1:0.1-0.15; The material I is a combination of the powder material and the liquid material.
Citation Information
Patent Citations
Crack self-repairing concrete and preparation and repairing method thereof
CN111072326A
Biological admixture for self-healing of concrete microcracks and preparation method of biological admixture
CN106830746A
Concrete crack self-healing agent and preparation method thereof
CN113264729A
Building waterproof self-repairing material and preparation method thereof
CN114105542A